CEO characteristics and corporate debt: An in-depth analysis in the Indonesian context - Heriyanto Heriyanto (Journal of Enterprise and Development (JED), 2024)
Purpose — This study aims to investigate differences in debt policies among companies listed on the Indonesia Stock Exchange, with a focus on gender and CEO tenure.Method — This research was carried out on non-financial companies listed on the Indonesia Stock Exchange from 2013 to 2022. The sampling method employed in this study was a purposive sampling approach. The initial sample comprised 86 companies, and the final sample consisted of 65 companies, yielding a total of 650 observations. The data analysis technique utilized in this study is the independent difference test, employing a nonparametric approach through the Mann-Whitney test.Result — This study revealed significant disparities in debt policies among companies listed on the Indonesia Stock Exchange, depending on the gender of the CEO. Specifically, male CEOs demonstrated a propensity to employ higher levels of debt compared to their female counterparts. Conversely, with regard to CEO tenure within the company, no significant difference was observed in relation to the company's debt policy.Novelty  — The novelty of this research lies in its emphasis on the importance of examining the gender and tenure of CEOs concerning the company's debt levels. The extended research period contributes a unique element by providing a more comprehensive perspective, and this is particularly noteworthy in the context of Indonesian studies, which have been relatively scarce and have yielded mixed results.